(untitled) (Revista cientifica In Vestigium Ire, 2019)
For the Colombian economy, the process of internationalization and, obviously, the opening of markets are two issues of special importance. Since 1991, Colombia is inserted in the world economy in a more aggressive and les shy manner, and since that year the internationalization process, driven by the willingness of governments towards world markets, has become evident in the development plans that Colombia has generated since that year; which have favored a growing external projection of the business network. Currently, the number of Colombian companies present in the world markets of goods and services has increased progressively. At the same time, the international aspect has become an important part of the companies’ strategy. However, Colombian presence abroad is still below its potential capacity, therefore, it is a priority in the upcoming years to continue with the efforts to expand the incursion of exporting companies in the global market and consolidate this international perspective through innovation as a fundamental element in this business internationalization. The article reflects the review exercise of recent literature on the subject, with the aim of identifying previous studies, which mention innovation as a fundamental element in the competitiveness of exporting companies.